Direct Measurement of the Impact of Teaching Experimentation in Physics Labs - Smith, Emily M.; Stein, Martin M.; Walsh, Cole; Holmes, N. G. (Physical review. X, 2020)
While there have been many calls to improve the quality of instructional physics labs, there exists little research on the effectiveness of lab instruction. This study provides a direct comparison between labs that have goals to reinforce physics content to those that emphasize experimentation skills. In this controlled study, all students attended the same lecture and discussion sections, had the same homework and exams, but attended labs that had one of two aims: teaching experimentation or reinforcing content. We compare students’ engagement with experimentation during the lab as well as the impacts on students’ exam performance and attitudes and beliefs about experimental physics. We find no measurable differences between lab conditions on students’ exam performance. Nonetheless, we find measurable and significant improvements in students’ engagement in expertlike experimentation practices and attitudes and beliefs about experimental physics for students in the experimentation labs. The benefits of the experimentation labs are stable across two subsequent semesters of implementation, as measured via standardized assessments. The results provide direct evidence of the extensive benefits of using labs to teach experimentation while directly demonstrating that shifting instructional goals and structure in labs can occur without cost to performance on course exams.